PENGARUH PENGETAHUAN KEUANGAN DAN SIKAP KEUANGAN TERHADAP PRAKTIK KEUANGAN SYARIAH MAHASISWA DI INDONESIA - Amir Hamzah; Nurfania Sukma; Firda Andini Nurfa’ijah; Sindi Aprilia (Jurnal Riset Keuangan dan Akuntansi, 2022)
The purpose of this study is to analyze the influence of financial knowledge and financial attitudes on sharia financial practices among Indonesian students. This research is a quantitative study using descriptive and verification research methods. Primary data was obtained using a questionnaire from a sample of 328 respondents from 25 provinces in Indonesia. Non-probability sampling with quota sampling techniques was used to select the sample. The data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with Smart-PLS software. The results showed that financial knowledge has a significant positive effect on sharia financial practices among Indonesian students. Additionally, financial knowledge has a significant positive effect on financial attitudes among Indonesian students, and financial attitudes have a significant positive effect on sharia financial practices among Indonesian students. Keywords: Financial Knowledge, Sharia Financial Practices, Financial Attitudes.